2016
DOI: 10.1080/10643389.2016.1272343
|View full text |Cite
|
Sign up to set email alerts
|

Peracids in water treatment: A critical review

Abstract: Peracids have gained interest in the water treatment over the last few decades. Peracetic acid (CH 3 CO 3 H) has already become an accepted alternative disinfectant in wastewater disinfection whereas performic acid (CHO 3 H) has been studied much less, although it is also already commercially available. Peracids have also been tested for drinking water disinfection, oxidation of aqueous (micro)pollutants, sludge treatment and ballast water treatment, to name just a few examples. The purpose of this review pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
122
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 256 publications
(145 citation statements)
references
References 211 publications
(295 reference statements)
2
122
0
1
Order By: Relevance
“…Batterman et al () reported that hydrogen peroxide concentrations below 4 mg/L did not result in aldehyde byproduct formation. A comprehensive review (Luukonen & Pehkonen, ) suggested that water disinfected with 10 mg/L of peracetic acid, containing hydrogen peroxide and carboxylic acid, could form 6.1 μg/L of formaldehyde.…”
Section: Resultsmentioning
confidence: 99%
“…Batterman et al () reported that hydrogen peroxide concentrations below 4 mg/L did not result in aldehyde byproduct formation. A comprehensive review (Luukonen & Pehkonen, ) suggested that water disinfected with 10 mg/L of peracetic acid, containing hydrogen peroxide and carboxylic acid, could form 6.1 μg/L of formaldehyde.…”
Section: Resultsmentioning
confidence: 99%
“…PFA has been estimated to be a cost-efficient option to replace PAA if the need for disinfectant is getting higher due to the increasing capacity of industrial plants, although it needs to be produced just before usage [29]. PFA, used in this study, was self-made with the reagent price around 15 € for 1 kg [24].…”
Section: Discussionmentioning
confidence: 99%
“…This may preferentially promote the anodic reactions, including the decomposition of H 2 O 2 and the oxidation of CH 3 COOH to molecules different from PAA. As the formation of PAA is directly linked to the production of H 2 O 2 and this production is expected to be mainly a cathodic process [especially taking into account the high sp 3 :sp 2 ratio of the BDD layers used (255) 20 ], a lower overall efficiency in the production of both oxidants can be explained for the jet device.…”
Section: Role Of the Reactor Configurationmentioning
confidence: 99%
“…The production of peroxoacetic acid (also peracetic acid, peroxyacetic acid, or PAA) is attracting increasing industrial interest due to its properties related to disinfection and bleaching and use as an oxidant agent . The in situ production of any chemical reagent is always favorable from the viewpoint of reducing the CO 2 footprint related to its transportation .…”
Section: Introductionmentioning
confidence: 99%